Methodological guidelines for coursework paper writing on "Management 5 (Performance Management)" course - Краснокутська, Наталія Станіславівна; Маковоз, Оксана Сергіївна; Ковшик, Валентин Ігорович (My University, 2021)
The aim of the coursework is to gain in-depth knowledge of the methodology, principles, and practices of business performance management with a focus on developing the ability to apply a variety of approaches for measuring it. The objectives of the coursework are about training professional managers who have modern knowledge, skills, and abilities in the field of business, who can effectively perform their functions in practice. Writing a coursework on the subject “ Management 5” is a generalization of the knowledge gained by students in the learning process on the subject area and the methodology of performance management. The coursework is obligatory for all students and counts towards final grade at the course level. The coursework includes written report and formal presentation. This task is an opportunity for students to read and think about the questions that were discussed in class, do a research, and get feedback.
Методичні вказівки до виконання курсової роботи з курсу "Менеджмент 5 (Управління результативністю)"
Keywords: methodological guidelines; performance; practical situations; business entity; objectives; target